PELAKSANAAN TIMBANG TERIMA KEPERAWATAN TERHADAP KEPUASAN KERJA PERAWAT - Perwirah, Ganda (Politeknik Kesehatan Kemenkes Bengkulu, 2015)
Hand over nursing is a way to convey and receive information related with aclient’s condition, so that the service to be provided can be justified as well as to givesatisfaction to the work performed. This study aimed to determine the relathionship betweenthe implementation nursing hand over the job satisfaction of nurses in hospital curup 2014.The study design used is descriptive method with cross sectional approach. Analyticalsamples are 79 nurses and sampling with purposive sampling proportional amples taken ineach room inpatients Curup hospital. Univariate analysis (94,9%) of nurses carrying out overhand receive and (44,1%) lower nurse job satisfaction. The results of the analysis with knownstatistical test Chi Square P value = 0,625 > 0.05 ; CI 9,5 % there is no relathionshipbetween implementation hand over accept the job satisfaction of nurses. Indicators of jobsatisfaction not only in the execution of the work, while the other factors that affect is apsychological factor, colleagues, promotion, and sallary / wages.